Validating and comparing stroke prognosis scales - Quinn, Terence J.; Singh, Sarjit; Lees, Kennedy R.; Bath, Philip M.W.; Myint, Phyo K. (American Academy of Neurology, 2017)
Objective: To compare the prognostic accuracy of various acute stroke prognostic scales using a large, independent, clinical trials dataset.